UTILIZATION OF OIL PALM EMPTY FRUIT BUNCH (OPEFB) FOR BIOETHANOL PRODUCTION THROUGH ALKALI AND DILUTE ACID PRETREATMENT AND SIMULTANEOUS SACCHARIFICATION AND FERMENTATION - Yanni Sudiyani; Euis Hermiati (Indonesian Journal of Chemistry, 2010)
Lignocellulosic biomass is a potential alternative source of bioethanol for energy. The lignocellulosics are abundantly available in Indonesia. Most of them are wastes of agriculture, plantation and forestry. Among those wastes, oil palm empty fruit bunch (OP EFB) is one of a potential lignocellulosics to be converted to bioethanol. This EFB, which is wastes in oil palm factories, is quite abundant (around 25 million tons/year) and also has high content of cellulose (41-47%). The conversion of OPEFB to ethanol basically consists of three steps which are pretreatment, hydrolysis of cellulose and hemicellulose to simple sugars (hexoses and pentoses), and fermentation of simple sugars to ethanol. Acid and alkali pretreatments are considered the simplest methods and are potentially could be applied in the next couple of years. However, there are still some problems that have to be overcome to make the methods economically feasible. The high price of cellulose enzyme that is needed in the hydrolysis step is one of factors that cause the cost of EFB conversion is still high. Thus, the search of potential local microbes that could produce cellulase is crucial. Besides that, it is also important to explore fermenting microbes that could ferment six carbon sugars from cellulose as well as five carbon sugars from hemicellulose, so that the conversion of lignocellulosics, particularly EFB, would be more efficient.